Validating quantitative micro-ultrasound method for monitoring the development of liver steatosis in mouse model - Ekwe, David (My University, 2024)
Non-alcoholic fatty liver disease (NAFLD) is a condition where the liver accumulates fat without the influence of alcohol. The exact cause of NAFLD is not well understood but it is linked to a syndrome of metabolic disorders that influence and significantly alter how the body metabolizes and stores fat. Given that NAFLD is a progressive disease, longitudinal in vivo studies are needed to track and understand how the disease evolves and how the preclinical models respond to therapeutic interventions. While liver biopsy and histologic analysis remain the gold standard for the diagnosis of NAFLD, its invasiveness and high sampling variability make it impractical for the serial assessments in longitudinal preclinical studies. Micro-ultrasound, a non-invasive imaging technique for research animals, is a promising technique for conducting longitudinal studies of NAFLD models. However, the level of accuracy of this technique is not confirmed. The objective of this study was to establish the validity of a reliable and reproducible method of detecting the presence of hepatic steatosis in mice using quantitative ultrasound technique. Ten mice on high fat diet (HFD) and ten on chow were studied for 12 weeks and five mice from each group were assessed using micro-ultrasound. B-mode images of the liver were acquired and used to calculate the hepatic-renal ratio (H/R). This parameter was correlated with the biomarkers of hepatic steatosis for validation. The HFD mice developed hepatic steatosis as evidenced by the increased lipid droplets in histologic analysis, higher serum ALT activity, increased liver triglyceride concentration and body fat composition. Quantitative ultrasound was able to reliably differentiate between fatty liver and healthy controls (fold change 2.36, p<0.001) in a manner that corresponds to the indications of other biomarkers of hepatic steatosis. The H/R ratio had a positive correlation with the body fat, liver triglyceride content, serum ALT and histological image analysis (R = 0.62, 0.46, 0.92, 0.88, respectively). The results of this study indicate that quantitative micro-ultrasound technique is a feasible non-invasive approach for longitudinal evaluation of intra hepatic fat in preclinical mouse models.
Keywords: NAFLD, Quantitative ultrasound, Hepatic-Renal ratio, mice, Hepatic steatosis, Image analysis, longitudinal study